High-yield bioproduction of virus-free virus-like P4-EKORhE multi-lysin transducing particles as an antimicrobial gene therapeutic - Ramirez-Garcia, Robert; Sagona, Antonia P.; Barr, Jeremy J.; Jaramillo, Alfonso (Frontiers in Cellular and Infection Microbiology, 2025)
A description of the construction of the bioengineered P4-EKORhE and a comprehensive method for producing very high yields (up to 1012 particles per millilitre) enable the use of virus-like particles to transduce genetically encoded antimicrobials through a combination of synthetic biology and optimised upstream and downstream processing. The final product, a gene-delivered antimicrobial in the form of the multi-lysin cassette, is fully functional before and after packaging within P4-EKORhE particles. The antimicrobial activity of the multi-lysin cassette, characterised by its lysis proteins, was tested in vivo in both pure bacterial Escherichia coli cultures and a model of phage infection in co-culture with A549 immortalised human epithelial tissue cells. This work exemplifies several bioproduction methods and demonstrates how the virology of the P4 and P2 phages can be harnessed to establish a bioprocess for producing transducing particles at very high yields, avoiding contamination by the natural virus while maintaining the antimicrobial effectiveness of the final product.